Synthesis, Structure of Me6[14]N4diene+(ClO4)2 and the Cyclic Voltammetry Measurement of its Copper(II) Complex - Bi, Jian-Hong; Chen, Yan; Huang, Zi-Xian; Cui, Man; Hu, Nai-Liang (Asian Journal of Chemistry, 2010)
The Me6[14]N4diene·(ClO4)2 (5,5,7,12,12,14-hexamethyl- 1,4,8,11-tetraazacyclotetradeca-4,11-diene·2ClO4) has been synthesized and determined by X-ray diffraction. The crystal is orthorhombic, space group P2(1)/c with unit cell parameters: a = 14.9753(6)Å, b = 9.2169(4)Å, c = 16.4902(9)Å, α = 90º, β = 90º, γ = 90º, V = 2276.07(18)Å3, Z = 8, Dc = 1.411 g/cm3, μ = 0.334 mm-1, T = 293(2) K, Mr = 241.69, F(000) = 1032, R = 0.0626 and wR = 0.1745. The cyclic voltammograms of its copper(II) complex has been investigated.